Translation Transformation: Quillbot and the Shifting Landscape of Arabic Language Learning - hasanah, safinah; Mahbub, Mahbub (Instructional Development Journal, 2025)
This study examines how using QuillBot impacts students' Arabic translation skills using a quantitative quasi-experimental methodology and a pretest-posttest questionnaire. Sixty students from KH. Mukhtar Syafaat University Banyuwangi participated in the study. They were divided into two groups: one used QuillBot, and the other used traditional methods for translation. The experimental group performed significantly better on the post-test than the control group, according to the statistics. QuillBot considerably enhanced pupils' Arabic translation abilities, according to independent t-test research (t-value = 5.47, p < 0.05). The results of tests for homogeneity and normality provided further evidence of the validity and trustworthiness of the data gathered. This study adds to the larger conversation about AI-assisted learning, especially as it relates to the understudied field of Arabic translation. The findings emphasize the importance of integrating AI tools while maintaining foundational language skills to prevent overreliance on digital platforms. Additionally, this research provides practical recommendations for educators on how to optimize the use of AI-based translation tools in Arabic language learning.